Preliminary Study on Participation of the Oil Palm Stakeholders toward the Implementation of Mechanization in Oil Palm Plantation - Z, Ain Sophia; J, Mohd Fauzie; Ayob, Mohammad Amizi (2016)
Malaysia is the second biggest country exporting oil palm after Indonesia. It has become the most important commodity crop in Malaysia. It also one of the main contributor of commodity to the agricultural sector. This sector is include as one of the of the field in National Key Economic Area (NKEA) to contribute for national income. The rapid expansion of oil palm plantations insist a high demand for foreign labour. Advisably the stakeholders to implement mechanization in the farm. However the implementing of mechanization were not promising in oil palm plantation eventhough mechanization can be improved the productivity of palm oil. However, the acceptance level in palm oil mechanization is still not promising. There, for this paper is to study the acceptance level in implementing mechanization in oil palm plantation. Face to face interview was conducted using a structured questionnaire with a total of 62 respondents among the oil palm stakeholders in Malaysia. The result indicate that the acceptance level of oil palm smallholders towards mechanization were still low in oil palm industry.